2014
DOI: 10.1016/j.pmrj.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Intradiskal Methylene Blue Treatment for Diskogenic Low Back Pain

Abstract: This small trial did not demonstrate overall clinical success of intradiskal methylene blue injection for patients diagnosed with diskogenic pain by diskography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…They concluded that the intradiscal MB injection is a minimally invasive treatment that is effective in the short term and is indicated for discogenic back pain but may lose its effectiveness long term. In a study with findings that are in contrast to ours, Levi et al 23 used a single intradiscal injection of MB in patients with discogenic LBP and found no improvement in pain. The difference between their findings and ours might be explained by the small sample size (16 patients) used in their study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…They concluded that the intradiscal MB injection is a minimally invasive treatment that is effective in the short term and is indicated for discogenic back pain but may lose its effectiveness long term. In a study with findings that are in contrast to ours, Levi et al 23 used a single intradiscal injection of MB in patients with discogenic LBP and found no improvement in pain. The difference between their findings and ours might be explained by the small sample size (16 patients) used in their study.…”
Section: Discussioncontrasting
confidence: 89%
“…33 The second study was a randomized placebo-controlled trial of intradiscal injection of 1 ml of 1% MB for the treatment of chronic discogenic LBP and demonstrated a reduction in the mean disability score from 48 to 13 after MB treatment and a definite improvement in physical function. 32 Levi et al 23 investigated the change in ODI score in patients with discogenic LBP after a single intradiscal injection of MB; they considered 30% improvement in function as the categorical success rate and less than 30% as the categorical failure. They reported that for the ODI, at 1, 2 and 6 months after the injection, the categorical success rates were 25%, 21%, and 33%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…reported a clinical trial with a cohort of eight patients with mental health issues, and their results revealed a success rate of only 13%, in contrast to the outcomes reported by Peng et al . In 2014, Levi et al . defined success as improvement of at least 30% on the VAS accompanied by improvement of at least 30% on the ODI, and they found that the success rate was only 19%, 21%, and 25% for the 1‐, 2‐, and 6‐month follow‐up times, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…One study was a clinical RCT, but we extracted the data for the intradiscal MB injection group only. Another study included 16 cases, but the follow‐up data were incomplete; thus, complete data were extracted for only 8 cases. The characteristics of the five studies are described in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation